Analisa Kontribusi Al-Biruni dan Relevansinya dalam Pembangunan Ekonomi Komtemporer - Mohammad Hanief Sirajulhuda; Syamsuri (Menara Tebuireng, 2019)
This study aims to analyze the economic thinking of Abu Al-Rayhan Muhammad bin Ahmad Al-Biruni (later Al-Biruni) and its relevance in the world of contemporary economics. This research is a character study through library research (penelitian kepustakaan) using qualitative methods with inductive data analysis techniques. The analysis of Al-Biruni's economic thinking is based on written references either by the book Al-Biruni itself or writing that discusses economic thinking. This study found that Al-Biruni's economic thinking was in four (4) themes. First, Human Resources (HR). Second, the urgency of cooperation. Third, handicraft and industrial activities, and fourth, money. The results found in this study are that of the four themes of thought, it is quite relevant to the world of contemporary economics as a solution in solving the economic crisis that occurred